Cyclone: an accessible pipeline to analyze, evaluate, and optimize multiparametric cytometry data - Patel, Ravi K.; Jaszczak, Rebecca G.; Im, Kwok; Carey, Nicholas D.; Courau, Tristan; Bunis, Daniel G.; Samad, Bushra; Avanesyan, Lia; Chew, Nayvin W.; Stenske, Sarah; Jespersen, Jillian M.; Publicover, Jean; et al. (Frontiers in Immunology, 2023)
In the past decade, high-dimensional single cell technologies have revolutionized basic and translational immunology research and are now a key element of the toolbox used by scientists to study the immune system. However, analysis of the data generated by these approaches often requires clustering algorithms and dimensionality reduction representation which are computationally intense and difficult to evaluate and optimize. Here we present Cyclone, an analysis pipeline integrating dimensionality reduction, clustering, evaluation and optimization of clustering resolution, and downstream visualization tools facilitating the analysis of a wide range of cytometry data. We benchmarked and validated Cyclone on mass cytometry (CyTOF), full spectrum fluorescence-based cytometry, and multiplexed immunofluorescence (IF) in a variety of biological contexts, including infectious diseases and cancer. In each instance, Cyclone not only recapitulates gold standard immune cell identification, but also enables the unsupervised identification of lymphocytes and mononuclear phagocytes subsets that are associated with distinct biological features. Altogether, the Cyclone pipeline is a versatile and accessible pipeline for performing, optimizing, and evaluating clustering on variety of cytometry datasets which will further power immunology research and provide a scaffold for biological discovery.